Fixed Drug Eruption Due to Doxycycline Postexposure Prophylaxis - Lee Nguyen; Catherine Diamond (Pharmacoepidemiology)
Doxycycline is a semi-synthetic antibiotic in the tetracycline family. The three common subtypes of tetracyclines include naturally occurring, semi-synthetic, and new agents. Each subtype shares specific commonalities but is substantially different in various clinical applications. The mechanism of antimicrobial activity is the same across subtypes. The structural changes to the core naphthacene ring do not alter the mechanism of action but are thought to alter the rates of adverse effects and mechanisms of resistance. Tetracyclines as a class are known to cause fixed drug eruptions, but the majority of these adverse effects were associated with naturally occurring tetracyclines. Semi-synthetic tetracyclines have limited reports of fixed drug eruptions. Here, we present a case of fixed drug eruption in a patient who previously had multiple treatment courses with doxycycline. The case involves the use of doxycycline not for the treatment of an infection but as postexposure prophylactic (PEP) antibiotic therapy to prevent the acquisition of a sexually transmitted infection. Doxycycline PEP has been shown to reduce the rate of bacterial sexually transmitted infection in men who have sex with men (MSM). Doxycycline PEP is a single dose taken orally within 24–72 h of unprotected sexual intercourse. The dosing structure allows for ease of adherence but also repeatedly exposes individuals to doxycycline, putting them at risk for adverse events such as fixed drug eruptions, as illustrated by this case report.